DEMINERALISASI DAN DEPROTEINASI KULIT UDANG SECARA KONTINYU PADA TAHAPAN EKSTRAKSI KITIN SECARA BIOLOGIS - waltam, deden rosid; Hermansyah, Heri; Setyahadi, siswa (Jurnal Sains dan Teknologi Indonesia, 2010)
Chitin extraction in industry has been conducted by chemical process. The process has been known as a harsh treatment that badly affected to chitin quality, equipment and the environment. Since the last decade biologically chitin extractionhas more attracted attention. The biologically chitin extraction was conducted by batch fermentation or subsequent-batch fermentation. Continous demineralization and deproteinization is a new inovation on biologically chitin production technology.This system promises as an alternative technology for overcoming problems of batch fermentation process and chemical process. The objectives of the experiment was to obtain the optimal condition for continous deminineralizationand deproteinization for producing chitin from Panaeus vannamei shrimp shells. Lactobacillus acidophilus FNCC 116 and Bacillus licheniformis F11.1 was used for demineralization and deproteination process respectively. The results showed that the best condition for continuous demineralization was 6,5% glucose feed, with 16 hours retention time. For continuous deproteinization, the best condition was with 12 hours retention time. The process could remove 92.95% ash and 91.40% protein. The chitin, ash, and protein content of chitin product was 96.69%, 1.44% and 1,76% respectively.